2008
DOI: 10.1159/000114193
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pulmonary Function in Open versus Laparoscopic Cholecystectomy: A Meta-Analysis of the Tiffenau Index

Abstract: Background: Available scientific literature about open cholecystectomy (OC) and laparoscopic cholecystectomy (LC) does not show univocal results in terms of postoperative pulmonary function. A meta-analysis was carried out to evaluate the postoperative pulmonary function after OC and LC focusing on the Tiffenau index. Methods: Electronic databases were consulted (Cochrane Library, Embase and Pubmed). Standardized mean difference (SMD) with 95% CI was calculated for the Tiffenau Index. The kappa test was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 52 publications
3
7
0
2
Order By: Relevance
“…Die postoperative Lungenfunktion ist nach laparoskopischen Verfahren deutlich weniger und kürzer eingeschränkt als nach vergleichbaren offenen Eingriffen. Da die Manipulation in der Nähe des Zwerchfells die Lungenfunktion zusätzlich beeinträchtigt, stellt sich dieser Vorteil der Laparoskopie bei Operationen im Oberbauch im Vergleich zu Eingriffen am Unterbauch deutlicher dar [2]. Die einzige absolute Kontra indikation der Laparoskopie ist der erhöhte Hirndruck ("intracranial pressure", ICP).…”
Section: Vor-und Nachteile Der Methodeunclassified
See 1 more Smart Citation
“…Die postoperative Lungenfunktion ist nach laparoskopischen Verfahren deutlich weniger und kürzer eingeschränkt als nach vergleichbaren offenen Eingriffen. Da die Manipulation in der Nähe des Zwerchfells die Lungenfunktion zusätzlich beeinträchtigt, stellt sich dieser Vorteil der Laparoskopie bei Operationen im Oberbauch im Vergleich zu Eingriffen am Unterbauch deutlicher dar [2]. Die einzige absolute Kontra indikation der Laparoskopie ist der erhöhte Hirndruck ("intracranial pressure", ICP).…”
Section: Vor-und Nachteile Der Methodeunclassified
“…Je langsamer das Blut in einem verletzten Gefäß fließt, desto mehr CO 2 kann resorbiert werden. Somit steigt mit zunehmenden IAP bei laparoskopischen Eingriffen an der Leber die Gefahr einer CO2 -Embolie. Eine kritische Grenze scheint ein IAP von 8 mmHg zu sein, unter der die Emboliegefahr gering ist.…”
unclassified
“…However, pneumoperitoneum may have an adverse effect on respiratory function [10][11][12]. There have been two randomized studies of gastric bypass and colonic resection, and a meta-analysis of cholecystectomy and respiratory function recovery, comparing laparoscopic and open surgery [13][14][15]. In these studies, early recovery of respiratory function was seen in studies of cholecystectomy and gastric bypass, which are upper abdominal operations [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that laparoscopic upper abdominal surgery confers an advantage in the early recovery of respiratory function. In general, respiratory function is examined with a respiratory function test or blood gas analysis [2,8,[13][14][15]; however, respiratory function tests cause severe pain during the early postoperative period, and the long-term placing of an arterial catheter or frequent puncture of the artery should be avoided. On the other hand, SaO 2 is regarded as a simple and noninvasive indicator of pulmonary gas exchange and is routinely performed after major operations in all hospitals [16].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that pulmonary function is more favorably preserved in laparoscopic cholecystectomy and colectomy compared to the open methods for healthy individuals. The values of FVC and FEV1 are reduced by almost 50% after open cholecystectomy as compared to only 19-27% after laparoscopic cholecystectomy [6,7]. Use of epidural anesthesia in order to reduce postoperative abdominal pain resulted in only partial restoration of vital capacity and a minimal increase in functional residual capacity [8].…”
Section: Discussionmentioning
confidence: 99%